Nuo teritorinio ruožo prie linijos: sienų sampratos pokyčiai Lietuvos Didžiojoje Kunigaikštystėje XIV-XVI amžiuje - Čelkis, Tomas (Lietuvos istorijos studijos, 2008)
According to the Poland and Western Europe historians' research works and empirical material, this article is an attempt to reconstruct the conception and vicissitude of the Grand Duchy of Lithuania’s (GDL) western border in the 14th-16th centuries. The state border delimitation process, the conception of the Lithuanian state’s territorial tribal conglomerate transformation into the territorial state, defined by the treated state borders conceptions, are detectable in this article. This article also discloses the state border delimitation definition in old languages, comparing it to our present-day terminology. In the second chapter of this article, old land line marking specialties, which show us the source of the state demarcation process, are discussed. In the 14th century, GDL and Mazovia delimitation processes help us develop old line marking succession. The first western border was fixed during the time of Vytautas. Based on this foundation, the border renovation took place in the second half of the 15th century. The renovation process, which was driven by internal colonization repression, expanded in the first half of the 16th century. Finally, in the 16th century, an inhabited frontier and detailed border marking by modern-day signs, some of which were political by nature, led to the rise of the linear border of the GDL.